The Intention to Conceal Does Not Always Affect Time Perception - Matsuda, Izumi; Nittono, Hiroshi (Frontiers in Psychology, 2021)
The display duration of stimuli is overestimated due to the increase in phasic arousal induced by the stimuli or high levels of background arousal. A previous study demonstrated that display duration of items (2 s) was overestimated when a participant attempted to conceal one of the items so as not to be detected in the concealed information test. As the time perception remained the same between the item to be concealed and the other items, the overestimation was thought to be due to the high level of background arousal under the conceal condition. Duration of 2 s may be too long to examine the phasic arousal effect induced by the concealed item. The present study conducted three online experiments with shorter durations, that is, each of three items was presented with duration of 1, 0.5, and 2 s in Experiments 1, 2, and 3, respectively. The participants were instructed to conceal one of the three items under the conceal condition and did not conceal any item in the innocent condition. The difference in time perception between the conceal and innocent conditions or between items under the conceal condition was observed in none of the three experiments. The result indicates that temporal overestimation does not occur when a participant is only concealing an object. Rather, temporal overestimation would occur only when the level of background arousal is amplified by the concealment.